Structural color in the Swallow Tanager (Tersina viridis): using the Korringa-Kohn-Rostoker method to simulate disorder in natural photonic crystals - D'ambrosio, Christian Nahuel (2018)
The plumage of birds often exhibits attractive color effects produced by the interaction of light with the photonic microstructure present in the feather barbs and barbules. This microstructure constitutes a natural photonic crystal that rejects radiation of wavelengths contained within the band gap, which significantly alters the observed coloration depending on the incidence conditions. In spite of the high degree of regularity exhibited by the barb's microstructure of many species, the disorder present in these natural photonic crystals might modify the reflected response. In this paper, we address the problem of modeling the electromagnetic response of a quasiordered photonic structure, using an electromagnetic method only suitable for strictly periodic structures. In particular, we simulate the reflected response of the plumage of the Swallow Tanager (Tersina viridis) by two different approaches. On the one hand, we compute the reflected response by averaging reflectance spectra calculated by the Korringa-Kohn-Rostoker method for different geometrical parameters. We also apply the inner extinction approximation, which represents imperfections in the structure by adding a small imaginary part to the dielectric constant of the inclusions. The agreement between the experimental and the simulated results evidences the potential of the proposed methods to reproduce the electromagnetic response of natural photonic structures.